Surface Characterization of NiTi Superelastic and Shape Memory Alloys After Electrolytic Polishing - Lopes,Natalia Isabel de Azevedo (2017)
For the biomedical application of NiTi alloys, an excellent surface finishing process is required to guarantee high corrosion resistance and biocompatibility, eliminating the allergenic and toxic effects associated with the release of nickel ions in the body. Electropolishing is a process that can reduce surface imperfections and form a thin protective layer of TiO2, even in complex-shaped devices. The main objective of our study was to find and report suitable parameters for electrolytic polishing of NiTi wires, in both the superelastic and shape memory states. The results indicate that electropolishing in a 3.5 mol•L-1 methanolic H2SO4 electrolyte at 20ºC can effectively reduce surface roughness, remove superficial nickel-rich layers and improve corrosion resistance for austenitic and martensitic NiTi alloys.